Problems in Efficient Development of Clean Energy in Xizang - Liu, Chengpeng; Wan, Li; LUOSONGZEREN (International Journal of Electric Power and Energy Studies, 2024)
As Xizang’s economic development enters the new normal stage, the extensive and highly polluting production mode in the past no longer meets the needs of high-quality economic development in Xizang. Therefore, there is an urgent need to reduce the consumption of traditional fossil energy, develop low-carbon and clean green energy, optimize the energy structure, and promote green and sustainable economic development.